Groundwater modelling and management - Ghosh, N. C. Dr.; Sharma, K. D. 1950- (Kapil Dev). (New Delhi Capital Pub. Co., 2006)
Contributed articles; with reference to India.
Keywords: Groundwater flow -- Mathematical models; Groundwater -- Computer programs